DIRECTIONS OF DEVELOPMENT OF SELECTED COMMUNES OF THE LUBELSKIE VOIVODESHIP IN THE OPINION OF THEIR RESIDENTS - Komor, Agnieszka; Janulewicz, Paweł (Acta Scientiarum Polonorum. Oeconomia, 2019)
The goal of the study was to identify the level of local development and assess the directions of activities affecting it from the point of view of residents representing the surveyed communes. The H1 research hypothesis – that there is a positive relationship between the pro-development activities preferred by the residents and commune’s current level of development – underwent verification. The research scope included 24 communes from the Lubelskie Voivodeship. The research basically covered 2017. This study utilized the Hellwig’s development model method and the questionnaire survey method. The Hellwig’s model method made it possible to divide the analysed units into four groups regarding their level of development. The survey was used to identify and evaluate activities which, in the opinion of the respondents, are supposed to boost the development of the communes in the future depending on the level of their development to date. As a result of the conducted research, no statistically significant differences were found between the respondents representing communes that differ in the level of local development in terms of evaluation of the importance of particular activities for the communes’ development.